THE EFFECTIVENESS OF DRAMA-BASED INSTRUCTION IN DEVELOPING TECHNICAL COLLEGE STUDENTS' SPEAKING FLUENCY - Zikriyoyeva Shakhzoda (Zamonaviy ta’lim va tilshunoslik rivoji, 2026)
This article examines the effectiveness of drama-based instruction as a methodological tool for developing the speaking skills and oral fluency of technical college students. Drama-based instruction provides a natural and interactive context for language use, allowing students to improve performance fluency, expand vocabulary, and significantly reduce psychological barriers. We analyze the theoretical foundations, such as the affective filter, and present practical activities including role-plays and simulations for integrating narrative and dramatic techniques into the English language classroom.